Zelda With a Pearl Earring - Schriefer, Natalie (Medium, 2024)
After Nixeu’s “ZELDA [Girl with a Pearl Earring]”
Keywords: dept.hhs

Self-Portrait in the Key of Masc by Natalie Schriefer - Schriefer, Natalie (HAD, 2024)
In the style of WCW’s “This is Just to Say” Today I donated the red dress I wore to that holiday party which you were probably hoping I’d wear again but the truth is I hated the sweetheart neckl
Keywords: dept.hhs

Close Reading: HOW WRITING BOOK REVIEWS MADE ME a BETTER WRITER - Schriefer, Natalie (Poets & Writers Magazine, 2024)
Keywords: dept.hhs

How to Handle Online Harassment When It Happens to You - Schriefer, Natalie (Wired, 2024)
41% of adults in the US have been harassed online. If your mentions, inboxes, and DMs are blowing up with hateful comments, here are the technological and psychological tools you need to weather the storm.
Keywords: dept.hhs; how-to; mental health; online harassment; social media; twitter

Video Game Music: Science Explains Why Playing Final Fantasy Songs Is Good for Your Brain - Schriefer, Natalie (Inverse, 2024)
Musical memories are relatively unharmed by dementia.
Keywords: dept.hhs

How To Navigate Your Kid’s Coming Out - Schriefer, Natalie (Scary Mommy, 2024)
Five tips for straight parents on how to make the process a little easier -- and what to say.
Keywords: dept.hhs